Factors associated with dropping out of the program for Bachelor’s and Licentiate’s Degrees in Mathematics Teaching at the Universidad Nacional de Costa Rica (UNA): Evidence from the 2016 Student Cohort - Zamora-Araya, José Andrey; Villalobos-Madrigal, Francisco José (Uniciencia, 2018)
This study addresses the problem of dropouts among students in the program for Bachelor’s and Licentiate’s Degrees in Mathematics Teaching of the Universidad Nacional de Costa Rica. It is intended to describe the 2016 cohort of students in the program, and identify factors associated with academic dropout through semi-structured telephone interviews conducted with dropouts. Among the variables considered for the descriptive analysis are the grades students obtained in their high school of origin, their admission exam scores, standardized scores, an index of social development, social class, sex, type of school financing, scholarship status, place of residence, and the number of credits for which a student enrolled and how many of them he or she earned. The investigation found that there are differences between dropouts and non-dropouts in terms of admission exam scores and the number of credits that students enrolled for and earned. In addition, dropping out is more frequent among women, students without a scholarship, and students from urban areas. Eleven dropouts were interviewed, and three of these cases were analyzed in detail; final results showed that vocational and economic factors, teaching methods, and unmet expectations of students about the program are the main factors associated with dropping out.